2022
DOI: 10.1155/2022/5187304
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 1b Participated in the Modulation of Hypoxia/Reoxygenation-Caused H9c2 Cell Apoptosis and Autophagy

Abstract: Myocardial ischemia/reperfusion (I/R) injury seriously threats the health and life of patients with ischemia heart disease. Herein, we probed the potential influence of myosin 1b (myo1b) on hypoxia/reoxygenation- (H/R-) stimulated cardiomyocyte H9c2 cell apoptosis and autophagy. After H/R stimulation, the myo1b mRNA level in H9c2 cells was tested via qRT-PCR. Myo1b overexpression plasmid (OE-myo1b) and small interfering RNA (siRNA) targeting myo1b (si-myo1b) were transfected into H9c2 cells to alter myo1b expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The cells were placed in a constant temperature incubator at 37˚C and 5% CO 2 , and were maintained in DMEM (Gibco; Thermo Fisher Scientific, Inc.) supplemented with 10% fetal bovine serum (HyClone; Cytiva). To simulate myocardial I/R in vitro , H9c2 cells at 80% confluence were transferred to serum- and glucose-free DMEM, and were cultivated in a hypoxic atmosphere of 0.1% O 2 , 95% N 2 and 5% CO 2 for 6 h. Subsequently, the cells were maintained in the incubator with normal DMEM under normoxic conditions in the presence of 95% air and 5% CO 2 for 12 h for reoxygenation ( 17 , 18 ). H9c2 cells in the control group were cultured under normal culture conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were placed in a constant temperature incubator at 37˚C and 5% CO 2 , and were maintained in DMEM (Gibco; Thermo Fisher Scientific, Inc.) supplemented with 10% fetal bovine serum (HyClone; Cytiva). To simulate myocardial I/R in vitro , H9c2 cells at 80% confluence were transferred to serum- and glucose-free DMEM, and were cultivated in a hypoxic atmosphere of 0.1% O 2 , 95% N 2 and 5% CO 2 for 6 h. Subsequently, the cells were maintained in the incubator with normal DMEM under normoxic conditions in the presence of 95% air and 5% CO 2 for 12 h for reoxygenation ( 17 , 18 ). H9c2 cells in the control group were cultured under normal culture conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In cervical cancer (CC), Myo1b was reported to promote cell proliferation, migration, and invasion through the activation of c-MYC, in turn contributing to cervical carcinogenesis and tumor development [ 19 ]. In the cellular myocardial ischemia/reperfusion (I/R) injury model, upon I/R stimulation, Myo1b expression was reduced, and overexpressing Myo1b prevented the hypoxia/reoxygenation-induced cardiomyocytes apoptosis and proliferation inhibition in H9c2 cells [ 21 ]. Notably, our previous study demonstrated that Myo1b was implicated in the activation of ARG2-mTORC1 signaling axis that promotes smooth muscle cell senescence and apoptosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%